Positive electrode material and method for manufacturing the same, and sodium ion battery
Patent Information
- Application Number
- JP2024012942
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-17
- Filing Date
- 2024-01-31
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-01-31
AI Technical Summary
【0012】 従来技術と比較して、本発明の有益な効果は、以下のとおりである。 1、本発明が提供する正極材料は、プルシアンブルー基体を二重被覆することにより、電気化学性能に影響を与えないことを基本として、プルシアンブルー正極材料が吸湿しやすいという問題を効果的に解決することができ、それにより正極材料の空気中での保存性と電気化学性能を効果的に向上させることができる。 2、本発明が提供する正極材料の製造方法は、プルシアンブルー基体の表面に2層の被覆層を均一に被覆することができるため、材料の吸湿性を効果的に抑制することができ、ステップが簡単である。 3、本発明の正極材料は、ナトリウムイオン電池に使用されるため、ナトリウムイオン電池が優れたサイクル性能と倍率性能を有することを確保することを基本として、高湿度環境下での保存性能を向上させることができる。
Smart Images

Figure 2025027943000002 
Figure 2025027943000003 
Figure 2025027943000004
Abstract
Description
[Technical field]
[0001] This application claims priority to a Chinese patent application having application number 202311041962.7, filed on August 17, 2023, the entire contents of which are incorporated herein by reference.
[0002] Technical Field
[0003] The present invention relates to the technical field of sodium ion batteries, and in particular to a positive electrode material and a method for producing the same, and a sodium ion battery. [Background technology]
[0004] Prussian blue (PB) is an important cathode material for sodium-ion batteries and is commonly known as Na x M a M' b (CN)6·zH2O can be used, where 0 <x<2、0<a<1、0<b<1、z> 0, and M and M' represent transition metals. The Prussian blue positive electrode material has the advantages of high theoretical capacity, large gap, adjustable chemical composition, good structural stability, etc., and exhibits excellent electrochemical performance. At the same time, the material has the advantages of being cheap, non-toxic and harmless, easy to manufacture, and low energy consumption, etc., and is a positive electrode material that is expected to be commercially applied in sodium ion battery research.
[0005] There are still problems to be solved in order to use Prussian blue as a positive electrode material for sodium-ion batteries. Prussian blue is usually produced by a simple chemical precipitation method, so there are vacancy defects and crystal water in the structure of the material, where the crystal water is composed of adsorbed water, interstitial water and coordinated water. The crystal water in the structure may have serious adverse effects on the electrode material and the electrolyte, such as affecting the movement of sodium ions, causing side reactions with the electrolyte, and generating gas that affects the safety of the battery. Most of the adsorbed water and interstitial water in the material can be removed by high-temperature heat treatment, but the dehydrated Prussian blue has strong hygroscopicity because it can rapidly absorb water when exposed to air. In the manufacturing process of sodium-ion batteries, Prussian blue must go through processes such as pulping, coating, rolling, slicing, winding / stacking, liquid injection, chemical conversion, and packaging. In these processes, most of the coating, rolling, slicing, and winding / stacking are exposed to the air environment. Due to the hygroscopic properties of Prussian blue, the processing performance of the pole pieces will be poor, and the adsorbed moisture will have a serious impact on its sodium storage performance and the safety of the battery.
[0006] It is with this in mind that the present invention is specifically proposed. Summary of the Invention [Problem to be solved by the invention]
[0007] The first object of the present invention is to provide a positive electrode material that can suppress the hygroscopicity of the material without affecting the electrochemical performance of Prussian blue, thereby effectively improving the storage stability in air and the electrochemical performance of the positive electrode material.
[0008] A second object of the present invention is to provide a method for preparing the above-mentioned positive electrode material, which has simple steps and is suitable for large-scale industrial production.
[0009] A third object of the present invention is to provide a sodium ion battery comprising the above positive electrode material and having excellent electrochemical performance. [Means for solving the problem]
[0010] In order to achieve the above object of the present invention, the following technical solutions are particularly used: The present invention provides a positive electrode material comprising a Prussian blue substrate, and a first coating layer and a second coating layer sequentially coated on a surface of the Prussian blue substrate, the material forming the first coating layer includes a polymer of tannic acid; The material forming the second coating layer includes at least one of hexadecylamine, octadecylamine, octadecylphosphonic acid, N-phenyltrifluoromethanesulfonimide, 1H,1H,2H,2H-perfluorodecyltriethoxysilane, and 1H,1H,2H,2H-perfluorodecanethiol.
[0011] The present invention further provides a method for producing the above-mentioned positive electrode material, the method comprising the steps of: Mixing tannic acid, formaldehyde, ammonium ions, a first solvent, and water to obtain a precursor solution containing tannic acid; A first reaction is performed between a Prussian blue substrate and the precursor solution containing tannic acid to obtain PB@TA; and performing a second reaction between the PB@TA, a material for forming a second coating layer, and a second solvent to obtain the positive electrode material. The present invention further provides a sodium ion battery comprising the above-mentioned positive electrode material. Effect of the Invention
[0012] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. The positive electrode material provided by the present invention is double-coated on the Prussian blue substrate, which can effectively solve the problem that the Prussian blue positive electrode material is easily absorbed by moisture without affecting the electrochemical performance, and can effectively improve the storage stability in air and the electrochemical performance of the positive electrode material. 2. The manufacturing method of the positive electrode material provided by the present invention can uniformly coat two layers on the surface of the Prussian blue substrate, so that the hygroscopicity of the material can be effectively suppressed and the steps are simple. 3. The positive electrode material of the present invention is used in sodium ion batteries, so as to ensure that the sodium ion batteries have excellent cycle performance and charge capacity, and can improve the storage performance under high humidity conditions.
[0013] Brief Description of the Accompanying Drawings In order to more clearly describe the specific embodiments of the present invention or the technical solutions of the prior art, the following briefly describes the accompanying drawings that need to be used in the description of the specific embodiments or the prior art. Of course, the accompanying drawings described below are some embodiments of the present invention, and those skilled in the art can think of other accompanying drawings based on these accompanying drawings without any creative efforts. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is an XRD diagram of PB and PB@TA@ODA in Example 1 of the present invention. [Diagram 2] FIG. 2 is a SEM image of PB@TA@ODA according to Example 1 of the present invention. [Diagram 3] 3 is a TG curve of PB and PB-7D according to Example 1 of the present invention. [Figure 4] TG curves of PB@TA@ODA and PB@TA@ODA-7D in Example 1 of the present invention. [Diagram 5] 1 is an optical photograph of the wetting angle of a positive electrode piece manufactured by the present invention using the PB of Example 1. [Figure 6] 1 is an optical photograph of the wetting angle of a positive electrode piece produced by the present invention using PB@TA@ODA of Example 1. [Figure 7] 6 shows the charge and discharge curves of sodium ion batteries prepared by using PB and PB@TA@ODA in Example 1 of the present invention respectively. [Figure 8]1 shows cycle curves of a sodium ion battery prepared by the present invention using PB of Example 1 and PB@TA@ODA. [Figure 9] 2 shows the charge and discharge curves of the sodium ion battery prepared by using PB-7D and PB@TA@ODA-7D in Example 1 of the present invention. [Figure 10] 1 shows cycle curves of sodium ion batteries prepared by the present invention using PB-7D and PB@TA@ODA-7D in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The technical solutions of the present invention will be described below clearly and completely in conjunction with the accompanying drawings and specific embodiments. Those skilled in the art will understand that the examples described below are only a part of the examples of the present invention, not all of the examples, and are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Based on the examples of the present invention, all other examples obtained by those skilled in the art without creative efforts belong to the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or equipment used, they are all conventional products available on the market.
[0016] In a first aspect, some embodiments of the present invention provide a positive electrode material including a Prussian blue substrate, and a first coating layer and a second coating layer sequentially coated on a surface of the Prussian blue substrate, The material forming the first coating layer includes a polymer of tannic acid; The material forming the second coating layer includes at least one of hexadecylamine, octadecylamine, octadecylphosphonic acid, N-phenyltrifluoromethanesulfonimide, 1H,1H,2H,2H-perfluorodecyltriethoxysilane, and 1H,1H,2H,2H-perfluorodecanethiol.
[0017] In the positive electrode material of the present invention, a polymer of tannic acid is uniformly and completely coated on the surface of the Prussian blue substrate to form a first coating layer, i.e., a tannic acid polymer layer, and a second coating layer is coated on the surface of the first coating layer and connected to the first coating layer by chemical bonding.
[0018] In the positive electrode material of the present invention, the surface of the Prussian blue substrate is double-coated, thereby changing the surface of the Prussian blue substrate from hydrophilic to hydrophobic. Research has shown that the positive electrode material provided by the present invention has little weight loss under conditions of 150-250°C after being left for 7 days under conditions of normal temperature, normal pressure and high humidity. Therefore, the positive electrode material provided by the present invention can effectively suppress hygroscopicity under environments of normal temperature, normal pressure and high humidity, and therefore can effectively solve the problem that the Prussian blue positive electrode material is easily hygroscopic, without affecting the electrochemical performance. As a result, the positive electrode material can be well stored in air and has excellent electrochemical performance.
[0019] In the positive electrode material of the present invention, the Prussian blue substrate is used as an active material, the first coating layer provides binding groups for the second coating layer, and the second coating layer forms a hydrophobic coating layer. Through the cooperation of the three, the Prussian blue-based positive electrode material has excellent electrochemical performance and good environmental protection performance at the same time.
[0020] In one preferred embodiment, the chemical formula of the Prussian blue substrate is Na x M a M' b (CN)6·zH2O, where M and M' are each independently selected from at least one of Ni, Cu, Fe, Mn, Co, and Zn; <x<2、0<a<1、0<b<1、z> It is 0. M and M' may be the same or different.
[0021] In one preferred embodiment, the Prussian blue substrate is Na x Fe a [Fe b (CN)6]·zH2O, Na x Mn a [Fe b(CN)6]·zH2O, Na x Ni a [Fe b (CN)6]·zHO and Na x Co a [Fe b (CN)6]·zH2O.
[0022] In a preferred embodiment, the particle size of the positive electrode material is 200-300 nm, typically but not limited to, for example, the particle size of the positive electrode material is 200 nm, 220 nm, 240 nm, 260 nm, 280 nm, 300 nm, or a range value consisting of any two of these values.
[0023] In one preferred embodiment, the thickness of the first coating layer is 3 to 4 nm, which is typical but not limiting, for example, the thickness of the first coating layer may be 3 nm, 3.5 nm, 4 nm, or a range value consisting of any two of these values.
[0024] In one preferred embodiment, the thickness of the second coating layer is 1 to 2 nm, which is typical but not limiting, for example, the thickness of the second coating layer may be 1 nm, 1.5 nm, 2 nm, or a range value consisting of any two of these values.
[0025] In the positive electrode material of the present invention, if the thickness of the first coating layer is too high, it will affect the interfacial transport of sodium ions, and if it is too low, a complete coating layer cannot be formed. If the thickness of the second coating layer is too high, it will affect the interfacial transport of sodium ions, and if it is too low, it will not have good hydrophobicity.
[0026] In a second aspect, some embodiments of the present invention further provide a method for producing the cathode material, the method comprising: Mixing tannic acid, formaldehyde, ammonium ions, a first solvent, and water to obtain a precursor solution containing tannic acid; A first reaction between a Prussian blue substrate (PB) and a precursor solution containing tannic acid to obtain PB@TA; and performing a second reaction between the PB@TA, a material for forming the second coating layer, and a second solvent to obtain a positive electrode material.
[0027] In the present invention, a precursor solution of tannic acid is reacted with a Prussian blue substrate first, and tannic acid, formaldehyde and ammonium ions undergo a Mannich reaction and condense to form a tannic acid polymer, and a uniform layer of tannic acid polymer is formed on the surface of the Prussian blue substrate to obtain a Prussian blue substrate coated with tannic acid polymer (PB@TA). Then, a hydrophobic material is used for coating, for example, octadecylamine undergoes a Michael addition reaction or a Schiff base reaction with the hydroxyl group or carbonyl group in the tannic acid polymer to form a second coating layer on the surface of the PB@TA, thereby obtaining a positive electrode material (PB@TA@ODA) with a double-coating structure.
[0028] In a preferred embodiment, the temperature of the first reaction and the second reaction are each independently 25 to 80°C, and the time of the first reaction and the second reaction are each independently 1 to 72 h, which is typical but non-limiting, for example, the temperature of the first reaction and the second reaction may each independently be 25°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, or a range value consisting of any two of these values, and the time of the first reaction and the second reaction may each independently be 1 h, 10 h, 20 h, 30 h, 40 h, 50 h, 60 h, 70 h, or a range value consisting of any two of these values.
[0029] In one preferred embodiment, the method further includes a first washing and a first drying after the first reaction, and further includes a second washing and a second drying after the second reaction, and preferably the drying temperature is 50 to 200°C.
[0030] In one preferred embodiment, the molar ratio of tannic acid to formaldehyde is (0.022-0.024):1, preferably 0.023:1.
[0031] In one preferred embodiment, the substance providing the ammonium ions comprises aqueous ammonia.
[0032] In a preferred embodiment, the concentration of the aqueous ammonia is 20 to 30 wt %, and the ratio of the amount of the aqueous ammonia to the amount of the tannic acid used is 1 mL:0.1 to 1 mmol, which is typical but not limiting, and for example, the ratio of the amount of the aqueous ammonia to the amount of the tannic acid used is 1 mL:0.1 mmol, 1 mL:0.3 mmol, 1 mL:0.5 mmol, 1 mL:0.7 mmol, 1 mL:1 mmol, or a range value consisting of any two of these values.
[0033] In one preferred embodiment, a method for producing a precursor solution containing tannic acid includes mixing an aqueous tannic acid solution, an aqueous formaldehyde solution, aqueous ammonia, a first solvent, and water to obtain a precursor solution containing tannic acid, and preferably, the concentration of the aqueous tannic acid solution is 0.01-0.02 mol / L, the concentration of the aqueous formaldehyde solution is 2-5 wt%, and the concentration of the aqueous ammonia is 20-30 wt%, and more preferably, the volume ratio of the aqueous ammonia to the aqueous tannic acid solution is 1:(15-25), and preferably 1:20.
[0034] In one preferred embodiment, the pH value of the first reaction system is 6-7. Tannic acid, formaldehyde and ammonium undergo a Mannich reaction and condense to form a polymer of tannic acid, and the above amount of aqueous ammonia can provide sufficient NH4+ to accelerate the reaction rate.
[0035] In a preferred embodiment, the mass ratio of the Prussian blue substrate to tannic acid is 1:(0.05 to 2), which is typical but not limiting, for example, the mass ratio of the Prussian blue substrate to tannic acid is 1:0.05, 1:0.08, 1:0.1, 1:0.2, 1:0.4, 1:0.6, 1:0.8, 1:1, 1:1.2, 1:1.4, 1:1.6, 1:1.8, 1:2, or a range value consisting of any two of these values, and preferably, the mass ratio of the Prussian blue substrate to tannic acid is 1:(0.15 to 0.2).
[0036] In a preferred embodiment, the mass ratio of PB@TA to the material forming the second coating layer is 1:(0.1 to 5), which is typical but not limiting, for example, the mass ratio of PB@TA to the material forming the second coating layer may be 1:0.1, 1:0.5, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5 or a range value consisting of any two of these values, preferably, the mass ratio of PB@TA to the material forming the second coating layer is 1:(0.8 to 1.2). In one preferred embodiment, the first solvent comprises ethanol.
[0037] In a preferred embodiment, the mass ratio of tannic acid to the first solvent is 1:(45 to 50).
[0038] In a preferred embodiment, the volume ratio of the first solvent to water is (0.01-1:1).
[0039] In one preferred embodiment, the second solvent comprises at least one of methanol, ethanol, ethylene glycol, acetone, and tetrahydrofuran.
[0040] In one preferred embodiment, the mass ratio of the material of the second coating layer to the second solvent is 1:(50-55).
[0041] In one preferred embodiment, the method for producing the Prussian blue substrate comprises a liquid phase method or a solid phase method.
[0042] In one preferred embodiment, the method for producing a Prussian blue substrate comprises the steps of: The method comprises the steps of obtaining a Prussian blue substrate after reacting an aqueous solution of Na4Fe(CN)6 with an aqueous solution of a soluble metal salt, Here, the soluble metal salt includes sodium citrate and at least one of a Ni salt, a Cu salt, an Fe salt, a Mn salt, a Co salt, and a Zn salt.
[0043] In one preferred embodiment, the method for producing a Prussian blue substrate comprises the steps of: ball milling Na4Fe(CN)6 and a metal salt to obtain a Prussian blue substrate; Here, the metal salt includes at least one of a Ni salt, a Cu salt, an Fe salt, a Mn salt, a Co salt, and a Zn salt.
[0044] In a third aspect, some embodiments of the present invention further provide a sodium-ion battery comprising the above-described cathode material.
[0045] By using the positive electrode material of the present invention in a sodium ion battery, it is possible to improve the storage performance of the sodium ion battery at room temperature, normal pressure, and high humidity, while ensuring that the sodium ion battery has excellent cycle performance and power supply performance. Hereinafter, the embodiments of the present invention will be described in detail in conjunction with the examples. Those skilled in the art will understand that the following examples are only used to illustrate the present invention, but should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If no manufacturer is specified for the reagents or equipment used, they are all conventional products available on the market. EXAMPLES
[0046] Example 1 The method for producing the positive electrode material provided in this embodiment is as follows: 4mmol of Na4Fe(CN)6·10H2O was dissolved in 200mL of deionized water to form solution A, 6mmol of FeSO4·7H2O and 15g of sodium citrate were dissolved in 200mL of deionized water to form solution B, solution A was added to solution B, and then the mixture was left to stand at room temperature (25℃) for 6h, after which it was separated into solid and liquid to obtain a filter cake, which was then centrifuged and washed three times with deionized water and absolute ethanol, respectively, and dried in a blower drying box at 80℃ for 12h to obtain Prussian blue substrate (PB)Na 1.54 Step S1 to obtain Fe[Fe(CN)6] 0.96H2O; Step S2: 2 mL of 0.015 M tannic acid aqueous solution, 1 mL of formaldehyde aqueous solution (3.7 wt%), 0.1 mL of ammonia water (concentration 25 wt%), and 3 mL of ethanol are added to 13 mL of deionized water and mixed thoroughly to obtain a tannic acid precursor solution, 0.3 g of Na1.54Fe[Fe(CN)6]·0.96H2O is added to the tannic acid precursor solution, and the mixture is stirred at room temperature (25 °C) for 24 h. After filtration, the mixture is vacuum dried at 80 °C to obtain PB@TA. Step S3 includes adding 0.3 g of octadecylamine to 20 mL of ethanol and dissolving it sufficiently to obtain an octadecylamine precursor solution, adding 0.3 g of PB@TA to the octadecylamine precursor solution, stirring at room temperature (25°C) for 24 h, filtering, and then drying in vacuum at 80°C to obtain a positive electrode material (PB@TA@ODA).
[0047] Example 2 The method for producing the positive electrode material provided in this embodiment is as follows: Under inert atmosphere, 5 mmol of MnCl2·4H2O and 5 mmol of Na4Fe(CN)6·10H2O were added into an agate ball mill bottle, the ball to material ratio was 1:20, and after ball milling at a speed of 300 r / min for 12 h, a mixture was obtained, which was first centrifuged and washed three times with absolute ethanol, then centrifuged and washed three times with deionized water, and then dried in a vacuum oven at 80 °C for 12 h to obtain Prussian blue substrate (PB)Na. 1.63 Step S1 to obtain Mn[Fe(CN)6] 1.41H2O; 2 mL of 0.015 M tannic acid solution, 1 mL of formaldehyde solution (3.7 wt%), 0.1 mL of ammonia water (concentration 25 wt%), and 3 mL of ethanol were added to 13 mL of deionized water and mixed thoroughly to obtain a tannic acid precursor solution. 1.63 Step S2: Mn[Fe(CN)6]·1.41H2O is added to the tannic acid precursor solution, stirred at 40 °C for 24 h, filtered, and dried in vacuum at 80 °C to obtain PB@TA; Step S3 includes adding 0.3 g of octadecylamine to 20 mL of ethanol and dissolving it sufficiently to obtain an octadecylamine precursor solution, adding 0.15 g of PB@TA to the octadecylamine precursor solution, stirring at 60°C for 24 h, filtering, and then drying in vacuum at 80°C to obtain a positive electrode material (PB@TA@ODA).
[0048] Example 3 The method for producing the positive electrode material provided by this embodiment is the same as that of Example 1, except that in step S2, Na 1.54 The only difference is that Fe[Fe(CN)6]·0.96H2O has a mass of 1 g.
[0049] Example 4 The method for producing the positive electrode material provided by this embodiment is the same as that of Example 1, except that in step S2, Na 1.54 The only difference is that the mass of Fe[Fe(CN)6]·0.96H2O is 0.025 g.
[0050] Example 5 The manufacturing method of the positive electrode material provided in this embodiment refers to Example 1, except that in step S3, the mass of PB@TA is 3 g.
[0051] Example 6 The manufacturing method of the positive electrode material provided in this embodiment refers to Example 1, except that in step S3, the mass of PB@TA is 0.06 g.
[0052] Example 7 The method for producing the positive electrode material provided by this embodiment is the same as that of Example 1, except that in step S2, Na1.54 The only difference is that the mass of Fe[Fe(CN)6]·0.96H2O is 0.1 g, and the mass of PB@TA in step S3 is 0.1 g.
[0053] Example 8 The method for preparing the positive electrode material provided in this embodiment refers to Example 1, except that in step S3, octadecylamine is replaced with octadecylphosphonic acid.
[0054] Example 9 The method for preparing the positive electrode material provided in this embodiment refers to Example 1, except that in step S3, octadecylamine is replaced with 1H,1H,2H,2H-perfluorodecanethiol.
[0055] Example 10 The method for preparing the positive electrode material provided in this embodiment refers to Example 1, except that in step S3, octadecylamine is replaced with N-phenyltrifluoromethanesulfonimide.
[0056] Comparison 1 The method for preparing the positive electrode material provided in this Comparative Example is the same as that in Example 1, except that in step S2, the formaldehyde aqueous solution and the ammonia water are not added.
[0057] Comparison 2 The method for producing the positive electrode material provided in this comparative example is the same as that in Example 1 except for removing steps S1 and S2, and using Prussian blue substrate (PB)Na 1.54 The only difference is that the sample PB@ODA can be obtained by directly carrying out step S3 on Fe[Fe(CN)6]·0.96H2O.
[0058] Test Example 1 XRD tests were carried out on the PB and PB@TA@ODA in Example 1, and the results are shown in FIG.
[0059] As can be seen from Figure 1, the structure of PB@TA@ODA has not changed significantly compared with that of PB and is still a pure cubic Prussian blue structure.
[0060] The PB@TA@ODA in Example 1 was examined by scanning electron microscope, and the results are shown in FIG.
[0061] As can be seen from Figure 2, the PB@TA@ODA still maintains a cubic shape.
[0062] Thermogravimetric tests were conducted on PB, PB-7D, PB@TA@ODA, and PB@TA@ODA-7D in Example 1, and the results are shown in Figures 3 and 4. Here, PB-7D indicates that PB was left at room temperature, normal pressure, and humidity of 80% for 7 days, and PB@TA@ODA-7D indicates that PB was left at room temperature, normal pressure, and humidity of 80% for 7 days.
[0063] As can be seen from Figures 3 and 4, sample PB-7D shows a significant weight loss at 150 and 250 °C, and the adsorbed water and interstitial water in the material increase significantly. Meanwhile, the TG curve of PB@TA@ODA-7D shows almost no change compared to PB@TA@ODA, indicating its excellent moisture absorption inhibition ability.
[0064] Test Example 2 The manufacturing method of the positive electrode piece is as follows: Weighing out the positive electrode material, conductive agent (Ketjen Black and Super P in a mass ratio of 1:1) and polyvinylidene fluoride (PVDF) in a mass ratio of 7:2:1, adding a certain amount of N-methylpyrrolidone (NMP) as a solvent, and grinding them to form a uniform slurry; The slurry is uniformly applied to an aluminum foil, and then baked at 70° C. for 24 hours; Finally, the method includes cutting the resultant into small disks having a diameter of 8 mm to obtain positive electrode pieces having a loading of 1.6 to 2.4 mg / cm2.
[0065] The manufacturing method of a sodium ion battery is as follows: Put the positive electrode piece into a 2032 type battery shell, use sodium piece as negative electrode, glass fiber as diaphragm, and foamed nickel as support piece; Dissolving 1 mol / L NaClO4 in EC (ethylene carbonate) and DEC (diethyl ethyl carbonate) in a volume ratio of 1:1, and adding 5% FEC (fluorinated ethylene carbonate) to obtain an electrolyte; and assembling the battery in a glove box filled with argon, and strictly controlling the moisture content in the glove box to less than 0.01 ppm and the oxygen content to less than 0.05 ppm to obtain a sodium-ion battery.
[0066] The packaged sodium battery is left at room temperature for 8 hours, and a charge / discharge test is performed using Wuhan Bluelight's CT2001 charge / discharge tester, with the charge / discharge voltage set to 2.0 V to 4.2 V. The cycle performance test is performed at a rate of 1 C (1 C = 170 mA g-1).
[0067] The PB and PB@TA@ODA in Example 1 are used as the positive electrode materials, and the positive electrode pieces are manufactured according to the above-mentioned manufacturing method of the positive electrode pieces. The wetting angle of the positive electrode pieces is tested, and the results are shown in FIG. 5 and FIG. 6.
[0068] As can be seen from Figures 5 and 6, Figure 5 shows the wetting angle of the positive electrode piece made of PB, which is 108°, and Figure 6 shows the wetting angle of the positive electrode piece made of PB@TA@ODA, which is 127°, which is much larger than that of the positive electrode piece made of PB, which shows that PB@TA@ODA has good hydrophobicity.
[0069] PB, PB-7D, PB@TA@ODA and PB@TA@ODA-7D in Example 1 were used as the positive electrode materials, respectively, to manufacture sodium batteries according to the above-mentioned manufacturing method for a sodium ion battery, and charge / discharge and cycle tests were performed on the sodium ion batteries, and the results are shown in Figures 7, 8, 9 and 10. Here, PB-7D indicates that PB was left at room temperature, normal pressure and humidity of 80% for 7 days, and PB@TA@ODA-7D indicates that PB was left at room temperature, normal pressure and humidity of 80% for 7 days.
[0070] As can be seen from Fig. 7 and Fig. 8, the initial discharge capacities of the sodium-ion batteries fabricated using PB and PB@TA@ODA, respectively, are 142 mAh g-1 and 150 mAh g-1, respectively, which are not significantly different, and the cycle performances are relatively similar.
[0071] As can be seen from FIG. 9, after being left for days, the initial discharge capacity of PB7 decayed to 116 mAh g-1, and its sodium storage performance was significantly reduced, while the initial discharge capacity of PB@TA@ODA-7D was still above 145 mAh g-1, showing almost no capacity decay compared with PB@TA@ODA, and better storage stability under normal temperature, normal pressure and high humidity environments.
[0072] As can be seen from FIG. 10, PB@TA@ODA-7D still exhibits very stable cycling stability, high initial efficiency, high specific capacity, and excellent hydrophobic performance as the positive electrode of a sodium ion battery.
[0073] The positive electrode materials prepared in Examples 1 to 10 and Comparative Examples 1 to 2 and the positive electrode materials left for 7 days were used to manufacture sodium batteries according to the above-mentioned method for manufacturing a sodium ion battery. Charge / discharge and cycle tests were performed on the sodium ion batteries, and the results are recorded in Table 1.
[0074] [Table 1]
[0075] As can be seen from Table 1, when Prussian blue is double-coated with an appropriate amount of tannic acid polymer and a second-layer coating material, it can exhibit good environmental preservation performance while exhibiting excellent electrochemical performance.
[0076] Although the present invention has been described in specific embodiments, it should be noted that the above embodiments are only used to describe the technical solutions of the present invention, and are not intended to limit them. Those skilled in the art should understand that, without departing from the spirit and scope of the present invention, the technical solutions described in the above embodiments can be modified or part or all of the technical features can be replaced equivalently, and these modifications or replacements do not cause the essence of the corresponding technical solutions to depart from the scope of the technical solutions of the embodiments of the present invention, and therefore the appended claims are intended to include all these replacements and modifications that fall within the scope of the present invention.
Claims
1. A Prussian blue substrate, and a first coating layer and a second coating layer sequentially coated on a surface of the Prussian blue substrate, the material forming the first coating layer comprises a polymer of tannic acid; A positive electrode material, characterized in that the material forming the second coating layer includes at least one of hexadecylamine, octadecylamine, octadecylphosphonic acid, N-phenyltrifluoromethanesulfonimide, 1H,1H,2H,2H-perfluorodecyltriethoxysilane, and 1H,1H,2H,2H-perfluorodecanethiol.
2. The chemical formula of the Prussian blue substrate is Na x M a M' b (CN) 6 ・zH 2 O, wherein M and M' are each independently selected from at least one of Ni, Cu, Fe, Mn, Co, and Zn, and 0<x<2, 0<a<1, 0<b<1, z>0; And / or the particle size of the positive electrode material is 200 to 300 nm.
3. 2. The positive electrode material according to claim 1, wherein the first coating layer has a thickness of 3 to 4 nm.
4. 2. The positive electrode material according to claim 1, wherein the second coating layer has a thickness of 1 to 2 nm.
5. Mixing tannic acid, formaldehyde, ammonium ions, a first solvent, and water to obtain a precursor solution containing tannic acid; A first reaction is performed between a Prussian blue substrate and the precursor solution containing tannic acid to obtain PB@TA; and a step of subjecting the PB@TAw, a material for forming a second coating layer, and a second solvent to a second reaction to obtain the positive electrode material.
6. the temperature of the first reaction and the second reaction is independently 25 to 80° C.; And / or the time of the first reaction and the second reaction are each independently 1 to 72 hours.
7. The molar ratio of the tannic acid to the formaldehyde is (0.022 to 0.024):1; The substance providing the ammonium ion includes aqueous ammonia (2); The method for producing a positive electrode material according to claim 5, characterized in that the method includes at least one of the characteristics (3), in which the concentration of the ammonia water is 20 to 30 wt %, and the ratio of the amount of the ammonia water to the amount of the tannic acid used is 1 mL:0.1 to 1 mmol.
8. the mass ratio of the Prussian blue substrate to the tannic acid is 1:(0.05-2); And / or, the mass ratio of the PB@TA to the material forming the second coating layer is 1:(0.1-5).
9. the first solvent comprises ethanol; 6. The method for producing a cathode material according to claim 5, wherein the second solvent comprises at least one of methanol, ethanol, ethylene glycol, acetone and tetrahydrofuran.
10. A sodium ion battery comprising the positive electrode material according to any one of claims 1 to 4.
Citation Information
Patent Citations
Preparation method of sodium ion battery negative electrode material, negative electrode material and sodium ion battery
CN113659143A
Hexacyanoferrate complex and lithium secondary battery using the same as anodic active substance
JP2001048527A
Electrode plate, secondary battery and its manufacturing method, and device including secondary battery
JP2023542595A